THE PRINCIPLES OF CHOICE OF ARMENIAN OBSIDIAN SOURCES IN BRONZE AGE, OBTAINED BY pXRF ANALYSIS (Proceedings of the YSU C: Geological and Geographical Sciences, 2018)
In the previous study an analytical database of geological obsidian samples was obtained within the method of portable X-ray fluorescence (pXRF). In this paper 292 obsidian samples from three settlements belonging to the Kura-Araxes culture were studied. Using the pXRF method, the chemical composition of these samples was compared with the results of geological ones to identify their sources. This will give a chance to understand the origin of the raw material.
Keywords: natural resources; obsidian; geochemical analysis; portable X-ray fluorescence; Bronze Age; Kura-Araxes